A Study of the Implementation of the Discovery Learning Model on the Speaking Skills of Class VIII Students at Madrasah Tsanawiyah Darul Ulum Sasa Ternate City - S Syamsia; Siska Febrianti Udin (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2022)
The aims of this research are to find out the percentage of students' speaking skills complete before and after using the discovery learning model at the students of Madrasah Tsanawiyah Darul Ulum Sasa and to find out whether the discovery learning model is effective in improving students' speaking skills or not. This research is descriptive in nature which aims to describe or describe the percentage of mastery values ​​of speaking skills before and after the use of the discovery learning learning model. The method used in this research is an experimental method of Quasi Experimental Research with a research design of